Reticulados ideais via corpos abelianos - Jorge, Grasiele Cristiane [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
O objetivo deste trabalho é o estudo de reticulados ideais. Neste estudo enfatizamos o artigo Lattices and Number Fields de Eva Bayer-Fluckiger, que apresenta alguns reticulados ideais com as mesmas propriedades que os reticulados Ap¡1, p primo, D4, E6, E8, K12 e ¤24.

The aim of this work is the study of ideal lattices. In this study we stress a Eva Bayer-Fluckiger's article \Lattices and Number Fields with presents some ideal lattices with same properties that lattices Ap¡1, p prime number, D4, E6, E8, K12 e ¤24.
Keywords: Álgebra; Teoria dos números; Teoria dos reticulados; Reticulados ideais; Corpos ciclotômicos; Ideal lattices; Diferent